0.65(m-11)+0.35m=-3.15

Simple and best practice solution for 0.65(m-11)+0.35m=-3.15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.65(m-11)+0.35m=-3.15 equation:


Simplifying
0.65(m + -11) + 0.35m = -3.15

Reorder the terms:
0.65(-11 + m) + 0.35m = -3.15
(-11 * 0.65 + m * 0.65) + 0.35m = -3.15
(-7.15 + 0.65m) + 0.35m = -3.15

Combine like terms: 0.65m + 0.35m = 1m
-7.15 + 1m = -3.15

Solving
-7.15 + 1m = -3.15

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '7.15' to each side of the equation.
-7.15 + 7.15 + 1m = -3.15 + 7.15

Combine like terms: -7.15 + 7.15 = 0.00
0.00 + 1m = -3.15 + 7.15
1m = -3.15 + 7.15

Combine like terms: -3.15 + 7.15 = 4
1m = 4

Divide each side by '1'.
m = 4

Simplifying
m = 4

See similar equations:

| -2.4=-0.9u+0.5u | | 6-10n=26 | | 2/7m-17=3/14 | | 7x-8y+5x-x+2y= | | 1.4=(-x)-3(1.4) | | 5x=(3x/2) | | (5/6) | | 15x^2+25x^6y^4=0 | | 4+7r=39 | | 21/30÷4/3 | | M-6.1=9.4 | | (2x/5)-(x/6)=-7/10 | | 9+3(z-3)=2z+3 | | 1.9n-48.4=3n | | 5.2+y=7.9 | | x^2+y^2=44 | | 4(3x)-8x/2=216 | | 2x+5x=42 | | (8/7)(8/7)= | | 27+t=-31 | | -83+5x=-2x+78 | | 8/7*8/7= | | 1-2x+2x=13 | | 7-7m=-5m+11 | | r-4x=10 | | (7x5)/5 | | S+42=18 | | 4x+6+3x+1=8x-2 | | b-3y=12 | | 11x-21=12+10x | | 1+3(4x-4)=11(2x-1) | | 3x/5=2.1 |

Equations solver categories